Kampung Pakelan: Khazanah Toleransi Antarumat Beragama dan Kepercayaan di Kota Kediri - Asyari, Asyari; Ilmi, Putri Wakhidatul; Aditya, Adam (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This research highlights the importance of understanding the local context in analyzing diversity and tolerance. Pakelan can already be said to be a village that meets the criteria of a miniature Indonesian state de jure and de facto. By using a phenomenological approach, this article aims to explore and portray the face of tolerance between religious communities and beliefs. The results of this research are first, the face of tolerance is attached to several activities in the form of ideas, ideas, and social activities, which manifest in the context of houses of worship, gametan, sacrifice, PHBA and so on. The conclusion of this research is that tolerance is not a static condition. The condition of tolerance and intolerance needs to be placed in a broader spectrum. A region can have a more tolerant character than other regions, but because no region is fully tolerant or intolerant, the position in the spectrum can change along with socio-political changes. The terms tolerance and intolerance should not be interpreted narrowly, only related to religious theological views. The theological orientation that exists in Pakelan does not necessarily prevent religious adherents and believers from coexisting with each other. Tolerance is a multidimensional condition, which is related to value, social and structural aspects.